The pianist - Polanski, Roman; Benmussa, Robert; Sarde, Alain, 1952-; Harwood, Ronald, 1934-; Brody, Adrien; Kretschmann, Thomas, 1962-; Finlay, Frank, 1926-2016; Lipman, Maureen; Fox, Emilia, 1974-; Stoppard, Ed; Rayner, Julia; Meyer, Jessica Kate; et al. (Universal, 2003)
Based on the memoirs of Wladyslaw Szpilman, a Polish Jew, who was a brilliant pianist. He watched as his family was shipped off to Nazi labor camps. He managed to escape and lived for years in the ruins of Warsaw, hiding from the Nazis.